Scratch Pemrograman Visual untuk Semuanya - Seng Hansun (Universitas Multimedia Nusantara, 2014)
In this modern era, the need to have a more tinkerable, more meaningful, and more social programming language has arisen. One of the programming environments that catch up with this issue is Scratch. In this paper, the author tries to explain Scratch as a visual programming language, its’ basic concepts, and its’ implementations. As an example, one interactive game that has been built using Scratch is shown at the end of this paper. Index terms - game, Scratch, visual programming.